Epithelial ovarian carcinoma in younger vs older women: is age an independent prognostic factor? The Hellenic Oncology Cooperative Group experience. Issue 5 (1st September 2007) - Pectasides, D.; Fountzilas, G.; Aravantinos, G.; Bamias, A.; Kalofonos, H. P.; Skarlos, D.; Briasoulis, E.; Konstantara, A.; Economopoulos, Th.; Dimopoulos, M. A.
Abstract : We retrospectively investigated the outcome of epithelial ovarian cancer (EOC) in women less than 45 years and over 70 years treated with cisplatin-based chemotherapy. We also investigated the impact of various factors on patients' survival. The tumor registry of the Hellenic Cooperative Oncology Group was used to identify women less than 45 years and over 70 years with EOC diagnosed between 1979 and 2004. Survival was calculated by the Kaplan–Meier method, and Cox proportional hazard models were used to determine the independent effect of each variable on survival. Of 1748 EOC patients, 200 were 45 or younger and 282 were over 70 years old. In the univariate analysis, younger age ( P < 0.001), better performance status (PS) ( P < 0.001), early stage ( P < 0.001), 0–2 cm residual disease ( P < 0.001), and well or moderate differentiation grade ( P = 0.004) were significant prognostic factors for improved survival. In the multivariate analysis, older age (hazard ratio [HR]: 1.88, 95% CI: 1.27–2.77, P = 0.002), advanced stage (HR: 2.87, 95% CI: 1.49–5.52, P = 0.002), PS >1 (HR: 1.91, 95% CI: 1.18–3.08, P = 0.008), and residual disease (HR: 1.46, 95% CI: 1.01–2.13, P = 0.046) were independently associated with inferior survival. With a median follow-up of 45 months (range 0.1–197 months), median survival (118.5 months) of younger patients differed significantly compared to that of older patients (33 months) ( P < 0.001). In conclusion, younger women with EOC have significantly improved survival compared to older patients. Age, PS, stage of the disease at diagnosis, and residual disease are important independent predictors for survival.